17th IEEE International Multi Topic Conference 2014 2014
DOI: 10.1109/inmic.2014.7097387
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Dynamic Line Rating technique in a 130 kV regional network

Abstract: Abstract-This paper investigates the possibility of using Dynamic Line Rating (DLR) to increase the existing power transmission capacity of overhead lines. The main contribution is to combine theoretical calculations and modeling with real application to conclude benefits of DLR. Both introduction of relevant theory and a case study on a power distribution system in Sweden are included. The concept of DLR implies that the capacity of a component dynamically varies as a function of external parameters, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Foss et al [6] characterized DLR calculation methods into two approaches: the conductor temperature approach that relies on conductor realtime current and temperature measurements, and the weather approach that calculates DLR from the ambient condition. Because conductor temperature measurements are normally not available, the weather approach is more widely used in dispatching studies, because measurements on conductors are not available and DLR is calculated from weather conditions such as air temperature, wind speed, and wind angle [7]- [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foss et al [6] characterized DLR calculation methods into two approaches: the conductor temperature approach that relies on conductor realtime current and temperature measurements, and the weather approach that calculates DLR from the ambient condition. Because conductor temperature measurements are normally not available, the weather approach is more widely used in dispatching studies, because measurements on conductors are not available and DLR is calculated from weather conditions such as air temperature, wind speed, and wind angle [7]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…By factoring in the cooling effect of wind, a 10-20% increase in the minimum line rating can be expected in windy areas [12], while a wind speed of 6m/s can at maximum double the line rating compared to the nominal case [10]. A case study showed that applying DLR to the 132kV line between Skegness and Boston enabled the grid integration of 20-50% more wind generation than by using the more conservative NLR [13], while another case study applied DLR to a 130 kV regional network and also showed that DLR is significantly profitable in the ampacity upgrading of overhead lines [11].…”
Section: Introductionmentioning
confidence: 99%
“…[59]- [61], and elevated temperature creep [56], [61]. Figure 1 illustrates that both atmospheric and conductor conditions [62]- [65] affect a conductor's line rating. Atmospheric conditions affect the line temperature and line rating, which can cause line to elongate and sag.…”
Section: Overhead Line Conductorsmentioning
confidence: 99%
“…the conductor current that produces maximum allowable conductor temperature at a specific location and time along the power line [7]) can be computed by DLR systems in order to utilize the conductor full capacity. Making better use of the "ampacity" using these systems has shown to return annual benefit of 35,000 USD/GWh as compared to conductor upgrading and the construction of new line which give an economic benefit of 17,000 USD/GWh and 11,000 USD/GWh, respectively [8].…”
Section: A Motivationmentioning
confidence: 99%